2021
DOI: 10.1177/10506519211021466
|View full text |Cite
|
Sign up to set email alerts
|

The Disappearance of Business Communication From Professional Communication Programs in English Departments

Abstract: Since 1985, the field of professional communication has grown in size and reputation while maintaining a space within its primary disciplinary home of the English department. This article relies on historical evidence to examine how a field that was once evenly divided between business communication and technical communication is now technical communication-centric, almost to the exclusion of business communication. The authors pose questions about the field of professional communication and how faculty who co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Other research found that students entering the workplace have knowledge gaps in business operations, problem-solving in industry, and project management (Stanton, 2017; Whiteside, 2003; Wilson & Ford, 2003). Some of these topics are not central to university pedagogies because it takes time for university curricula to integrate research focuses into pedagogy (Agboka & Dorpenyo, 2022; Dubinsky & Getchell, 2021). And areas such as business operation practices and the intricacies of industry problem solving would always be difficult to fully integrate into university curricula, given the diversity of TPC workplaces and the fast-paced changes in industry.…”
Section: Introductionmentioning
confidence: 99%
“…Other research found that students entering the workplace have knowledge gaps in business operations, problem-solving in industry, and project management (Stanton, 2017; Whiteside, 2003; Wilson & Ford, 2003). Some of these topics are not central to university pedagogies because it takes time for university curricula to integrate research focuses into pedagogy (Agboka & Dorpenyo, 2022; Dubinsky & Getchell, 2021). And areas such as business operation practices and the intricacies of industry problem solving would always be difficult to fully integrate into university curricula, given the diversity of TPC workplaces and the fast-paced changes in industry.…”
Section: Introductionmentioning
confidence: 99%